Effects of postharvest storage and dips in calcium salts on fresh-cut cantaloupe (Cucumis melo L. reticulates cv. Glamour) - Zainal Abidin, Munira (2012)
Extending the postharvest storage of the whole fruits at an optimum temperature (10 °C) may decrease the quality of the fruit itself. In this study, postharvest storage and Ca salts were applied to the whole fruit and fresh-cut cantaloupe, respectively, in order to observe the shelf life and to reduce the changes in quality during storage. The observations of the quality of the fresh-cut cantaloupe were carried out every 3±1 days for the physico-chemical (firmness, colour, total soluble solids content (TSS), titratable acidity (TA), and pH), microbiological (total plate counts (TPC) and yeast and moulds (YM)), and sensory analyses during storage at 2 °C and 87% relative humidity (RH) for 19 days. The firmness of the fresh-cut cantaloupe decreased as postharvest storage of the whole fruit and the storage time of the fresh-cut increased. By using a Ca chloride dipping treatment, a higher level of firmness maintenance of the fresh-cut cantaloupe was observed compared to the samples dipped in Ca lactate. Both the TPC and YM counts increased significantly during storage. The microbial growth of the fresh-cut cantaloupe prepared within one week and treated with Ca chloride can be consumed after up to 15 days of storage, while after more than one week of postharvest storage (W2, W3, and W3), the consumption period of the fresh-cut treated with both types of Ca salts decreased to 12 days of storage. Trained panellists also scored higher firmness and lower juiciness in the samples treated with Ca chloride and prepared within three weeks of postharvest storage. The colour and chemical properties of the fresh-cut cantaloupe were not significantly different (P<0.05) between both types of Ca salt treatment. The TSS increased and the TSS:TA ratio decreased significantly over the postharvest storage period of the whole fruit. No significant difference (P<0.05) between treatments was observed in terms of colour and the other chemical properties as the postharvest storage period of the whole fruits increased. In conclusion, the freshcut cantaloupe treated with Ca salts and kept for three weeks of postharvest storage resulted in a reduced amount of quality degradation and were acceptable for consumption.